2020
DOI: 10.15244/pjoes/105419
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Water Harvesting from the Atmosphere Using Solar-Powered Thermoelectric Modules

Abstract: The purpose of this study was to investigate the possibility of solar-powered thermoelectric elements (Peltier) to harvest water from the atmosphere. An Arduino-controlled model capable of harvesting water from air was designed and used in laboratory experiments. The developed prototype system was analyzed by using a package program using computational fluid dynamics. During the experiments, temperature and humidity data were recorded on a computer. We found that the Peltier used in the system developed temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Found that the water from AWG have the following analysis : pH [6.5], TDS [27]ppm, Mn [7]ppb , Mg[933]ppb , Ca [5080]ppb, Cu [19]ppb. They reported that water collected from AWG met the World Health Organization's drinking water standards and can be used for drinking after the required microbial processes [37].…”
Section: Water Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Found that the water from AWG have the following analysis : pH [6.5], TDS [27]ppm, Mn [7]ppb , Mg[933]ppb , Ca [5080]ppb, Cu [19]ppb. They reported that water collected from AWG met the World Health Organization's drinking water standards and can be used for drinking after the required microbial processes [37].…”
Section: Water Characterisationmentioning
confidence: 99%
“…Designed and manufactured solar-powered TEC air water generator. They concluded that water harvesting can be done with solar-power Peltier modules [19]. Proposed a small scale prototype based on using one TEC device, driven by a solar panel module.…”
mentioning
confidence: 99%
“…Consequently, many shortcomings of experiments and theoretical analysis could be overcome. Therefore, CFD is widely used in various flow field studies as it is a low-cost, shortterm and high efficiency method for obtaining the data during the flow field [2].…”
Section: Introductionmentioning
confidence: 99%